Claims Settlement and Risk Attitudes: Evidence from Selected Motor Insurance Policyholders in Lagos State, Nigeria - Ajemunigbohun, Sunday Stephen; Olowokudejo, Folake Feyisayo; Ukpong, Mfon Sampson (The Journal of Accounting and Management, 2022)
Claims, being the heartbeat of the workability of insurance, are the most critical contact influencer between the insuring public and the insurer. It serves as a critical path to truth that shapes the policyholders’ ultimate perceptions of their insurers. Therefore, this study aimed at evaluating the relationships between claims settlement and risk attitudes, with specific reference to motor insurance policyholders in Lagos, Nigeria. The study adopted a cross-sectional survey research design. The study population consisted of the total number of registered motorists recorded in 2019 by the Motor Vehicle Administration Agency to be 704,828. Thus, quota and convenience sampling methods were adopted in the questionnaire distribution and collection processes. A structured questionnaire was employed for data gathering. A total of 399 copies of the questionnaire were distributed, of which 287 were found usable which represented a 72% response rate. The data procedural technique employed were simple frequency percentages and the multinomial logistics regression method. The finding affirmed that claims settlement was significant in attracting reasonable risk attitudes from motor insurance policyholders. This study recommended that motor insurance providers should put in place fascinating claims packages in order to boost the confidence level of the motoring communities. Government should rejuvenate and empower the motor insurance public complaint commission to address issues relating to motor insurance claims of either party in the motor insurance contract. Given the implications of this study, future research work could direct attention to insurance fraud issues emanating from the insurance claims settlement manual.